(untitled) (Estudios de Historia de España, 2023)
The Napoleonic invasion generated in the Hispanic Monarchy a political and social division between those who defended the interference of the foreign king and the liberals and absolutists who had joined in a kind of tacit alliance whose aim was to banish José I. The historiography about the topic has been crossed by this division that favored a number of studies on the period. However, the educational issue was not always approached with the same intensity, generating vacancy areas that require deep rethinking about the legacies of an era. This paper proposes an analysis of the historiographic production that took education as its field of study during the interregnum of 1808-1814. To do this, we resort to a bibliographic search in two directions: the exploration through search engines and institutional repositories and the search in external references, that is, the search for citations and bibliographic references.